Coronary heart disease and stroke in the Sami and non-Sami populations in rural Northern and Mid Norway—the SAMINOR Study. Issue 1 (12th May 2020) - Siri, Susanna R A; Eliassen, Bent M; Broderstad, Ann R; Melhus, Marita; Michalsen, Vilde L; Jacobsen, Bjarne K; Burchill, Luke J; Braaten, Tonje
Abstract : Background: Previous studies have suggested that Sami have a similar risk of myocardial infarction and a higher risk of stroke compared with non-Sami living in the same geographical area. Design: Participants in the SAMINOR 1 Survey (2003–2004) aged 30 and 36–79 years were followed to the 31 December 2016 for observation of fatal or non-fatal events of acute myocardial infarction (AMI), coronary heart disease (CHD), ischaemic stroke (IS), stroke and a composite endpoint (fatal or non-fatal AMI or stroke). Aim: Compare the risk of AMI, CHD, IS, stroke and the composite endpoint in Sami and non-Sami populations, and identify intermediate factors if ethnic differences in risks are observed. Methods: Cox regression models. Results: The sex-adjusted and age-adjusted risks of AMI (HR for Sami versus non-Sami 0.99, 95% CI: 0.83 to 1.17), CHD (HR 1.03, 95% CI: 0.93 to 1.15) and of the composite endpoint (HR 1.09, 95% CI: 0.95 to 1.24) were similar in Sami and non-Sami populations. Sami ethnicity was, however, associated with increased risk of IS (HR 1.36, 95% CI: 1.10 to 1.68) and stroke (HR 1.31, 95% CI: 1.08 to 1.58). Height explained more of the excess risk observed in Sami than conventional risk factors. Conclusions: The risk of IS and stroke were higher in Sami and height was identified as an important intermediate factor as it explained a considerable proportion of the ethnic differences in IS and stroke. The risk of AMI, CHD and the composite endpoint was similar in Sami and non-Sami populations.